Nevalstisku organizāciju nozīme starptautiskajās tiesībās - Studāne, Agnese (Latvijas Universitāte, 2010)
Nevalstisko organizāciju (NGO) ietekme starptautiskajās tiesībās ir vērā ņemama, jo tās sekmē starptautiskās attiecības, apgādājot starptautiskos subjektus ar profesionāliem viedokļiem, ekspertīzēm un informāciju, kas bieži vien nebūtu valstu spēkos. NGO veido koalīcijas, kampaņas un informē sabiedrību svarīgos jautājumos. Sadarbība ar starptautiskiem subjektiem notiek abpusēja labuma gūšanas nolūkos. Lai arī iepriekšminētās aktivitātes ir nozīmīgas, NGO nav formāla statusa starptautiskajās tiesībās, par cik tām nav pienākumu ne pret valstīm, ne starptautiskajām organizācijām.

NGO influence is considerable and they have earned increasing worldwide attention by affecting international negotiations and advancing interests important to their constituencies. NGOs provide professional advice, expertise in a way public institutions would not be able to explore. NGOs make coalitions, campaigns and inform the public of important issues. NGOs and subjects of international law work hand in hand - NGO can reach their goals, while countries and international organizations can improve their position to make international treaties equitable and democratic. Although NGOs carry out all previous activities, they are informal and are liable only to the domestic law, since they don’t have formal commitment neither to countries nor to international organizations.
Importance of non-governmental organizations in international law
Keywords: Juridiskā zinātne